2014
DOI: 10.1123/ijsnem.2013-0248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Reduced-CHO Diet on the Rate of Perceived Exertion Curve During an Incremental Test

Abstract: The objective of this study was to evaluate the effect of a reduced-carbohydrate (reduced-CHO) diet on the rate of perceived exertion (RPE) curve during an incremental test. Nine physically active men performed a progressive incremental test on a cycle ergometer (25 W · 2 min(-1)) after 72 hr on either a control diet (60% CHO) or a reduced-CHO diet (30% CHO). Lactate and RPE thresholds were identified using the Dmax method (DmaxLa and DmaxRPE, respectively). Power output, heart rate and RPE scores in DmaxLa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
2
8
0
3
Order By: Relevance
“…Therefore, fatigue during SE may be related to other factors such as a better metabolite balance, reduced exercise-induced strain and maintenance of excitation-contraction coupling (8). Additionally, the higher CHO availability can also play a central role by reducing the perceived effort during exercise, thus increasing the fatigue tolerance (8,19,20). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fatigue during SE may be related to other factors such as a better metabolite balance, reduced exercise-induced strain and maintenance of excitation-contraction coupling (8). Additionally, the higher CHO availability can also play a central role by reducing the perceived effort during exercise, thus increasing the fatigue tolerance (8,19,20). …”
Section: Discussionmentioning
confidence: 99%
“…Nutritional interventions by handling carbohydrate (CHO) availability has also played a critical role in post-exercise metabolism ( 6 ). Endogenous CHO availability is commonly manipulated as follows: 1) by an 8–12 h fasting period before training, reducing liver but not muscle glycogen ( 7 ); 2) by reducing CHO diet content for a few days, reducing mainly liver glycogen ( 8 ); 3) by performing a pre-exercise before the main exercise to reduce pre-exercise liver and muscle glycogen ( 9 ); 4) or by a combination of two or more of those approaches ( 6 , 9 ). Regardless of the different ways to manipulate CHO stores, some evidence suggests that fat oxidation over the 24-h post-exercise period is increased when exercise is performed with a certain level of CHO depletion ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study, a strong significant correlation was discovered between the intensity of occurrence of both thresholds when they were expressed by absolute Hr ( = 0.83; p < 0.05) (Figure 2). Fabre et al [7] found the D max rPE at the same intensity as the LT. similarly, Ferreira et al [17] observed that the intensity of occurrence of the D max rPE and the LT was the same, independently of the pre-exercise carbohydrate availability, which suggests that the AnT can be estimated by the rPE scale alone.…”
Section: Discussionmentioning
confidence: 78%